2014
DOI: 10.4066/amj.2014.2070
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral variations of brachial plexus involving the median nerve and lateral cord: An anatomical case study with clinical implications

Abstract: During the routine dissection of upper limbs of a Caucasian male cadaver, variations were observed in the brachial plexus. In the right extremity, the lateral cord was piercing the coracobrachialis muscle. The musculocutaneous nerve and lateral root of the median nerve were observed to be branching inferior to the lower attachment of coracobrachialis muscle. The left extremity exhibited the passage of the median nerve through the flat tendon of the coracobrachialis muscle near its distal insertion into the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
(10 reference statements)
1
8
0
3
Order By: Relevance
“…In 7 [10%] specimens the median nerve is formed in the arm in front of the brachial artery instead in axilla. Similar findings were reported earlier [8,10,20,12,21]. In the present study, musculocutaneous nerve was found to be not piercing the coracobrachialis in 3 [4.28%] limbs which is similar to the findings of Jamuna M (6%, n=50) [17], Kishore C K (7.5%, n=40) [22], Shiv Goel [9] and Girish V Patil [23].…”
Section: Methodssupporting
confidence: 81%
“…In 7 [10%] specimens the median nerve is formed in the arm in front of the brachial artery instead in axilla. Similar findings were reported earlier [8,10,20,12,21]. In the present study, musculocutaneous nerve was found to be not piercing the coracobrachialis in 3 [4.28%] limbs which is similar to the findings of Jamuna M (6%, n=50) [17], Kishore C K (7.5%, n=40) [22], Shiv Goel [9] and Girish V Patil [23].…”
Section: Methodssupporting
confidence: 81%
“…Therefore, it becomes important to have knowledge regarding the normal anatomy as well as any observed variations in the muscle. 18 Fig. 3 Communication between the median nerve (MN) and the musculocutaneous nerve(MCN).…”
Section: Discussionmentioning
confidence: 99%
“…Butz et al [2] state that signalling mechanisms during embryological development might play a role during the fifth week of development, axons of the spinal nerves grow distally to initiate contact with the mesenchyme of the limb, and inadequate signalling may negatively influence the normal formation of the plexus.…”
Section: Discussionmentioning
confidence: 99%
“…Other variations have been described, the most common being the anatomical variation in the origin of the median and MNs, in which the lateral cord of the brachial plexus pierced the coracobrachialis muscle and then bifurcated in the middle third of the arm into two terminal branches originating the median and MNs [1,2]. Our finding differs from these studies as the lateral cord did not pierce the coracobrachialis muscle but involved it, and then bifurcated inferiorly into two terminal branches, the median and MNs.…”
Section: Discussionmentioning
confidence: 99%